Conditions of Spanish amateur boxing in the 1980s - Calle-Molina, M. T.; Martínez-Gorroño, M. E. (Journal of Human Sport & Exercise, 2023)
This research exposes the diverse sporting, social, economic, and political circumstances that amateur boxing experienced during the 1980s and early 1990s in Spain. This qualitative research is framed in the History of the Present Time and used the testimony of six oral sources, three of them Olympic boxers contemporary to the period under study. The results show that boxing began to be understood as a violent practice by some sectors of the Spanish population and its practice was banned in some parts of Spain. Its dissemination in the press and public television diminished notably and a gap was opened between professional boxing and amateur boxing in the popular ideology, understanding both with the differences that identified them, since the former began to be vilified, which negatively affected amateur boxing. These circumstances began to change in the 1990s, as boxing began to be used as a form of self-defence and was included in sports complexes for purposes other than competition. We can conclude that, despite the fact that in the 1980s the Spanish sport experienced a definitive boost, the circumstances described above were especially detrimental to amateur boxing in terms of the recruitment of practitioners and with respect to the economic support necessary for technicians and gyms in which they developed their pugilistic practice, which continued to be constituted as exclusive boxing halls located in marginal neighbourhoods.